(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is about the problems of translation practice. Translation demands a deep understanding of both grammar and culture. Translators need to know the rules of a language as well as the habits of the people who speak it. And even for the most experienced professionals, confusion and frustration are familiar feelings. French or every other language has its specific structure that complied with agreed rules and might have vast differences from each other. For example, in English, the adjective sits before the noun, but in French, an adjective is placed after a noun. As a result, linguists frequently have to add, remove, or rearrange source words to make the communication more natural.